Coping and emotion regulation in response to social stress tasks among young adolescents with and without social anxiety. Issue 1 (2nd January 2023) - Masters, Mitchell; Zimmer-Gembeck, Melanie J.; Farrell, Lara J.; Modecki, Kathryn L.
Abstract: Given that threat appraisal and coping are amenable to intervention, we aimed to identify threat appraisals and coping responses of anxious adolescents, relative to less anxious peers, during induced social stressors. Adolescents ( N = 76; Mage = 13.5yrs) completed a clinical interview and five stress tasks. After each task, we measured threat appraisals (state anxiety and social evaluation), general coping ability, and eight ways of coping and regulating emotion. Adolescents with high anxiety appraised more threat and used more distraction, behavioral disengagement and rumination. As adolescents progressed through tasks, threat appraisal decreased, perceived coping ability increased, and problem-solving, distraction, behavioral disengagement and rumination decreased. Social anxiety level × task interactions were not significant. In person-centered analysis, adolescents were distinguished as active copers, suppressors, or expressives. Anxious adolescents were more likely to be active copers, whereas their less anxious peers more likely suppressed or expressed emotions to cope with the tasks.